The Influence of Differentiated Instruction on the Learning Outcomes of Islamic Religious Education Subject at SMP Negeri 1 Bansari - Aisyah, Aida Aisyah; Luluk Ifadah; Zaidatul Arifah (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research investigates the impact of implementing differentiated learning on the learning outcomes of Islamic Education subject at SMP Negeri 1 Bansari. The study utilizes an experimental method, with the experimental class receiving additional treatment compared to the control class. Quantitative data collection techniques including observation, tests, and documentation are employed, with analysis involving prerequisite, normality, and hypothesis testing. The population comprises seventh-grade students, with thirty students each in the experimental and control classes. Results indicate that the experimental class, implementing differentiated learning, achieved higher average post-test scores (76.5) compared to the control class (64.2) using the lecture method. Statistical analysis confirms a significant influence of differentiated learning on learning outcomes (t-value > t-table value, 13.141 > 2.763, n=30, p<0.05). The findings suggest that implementing differentiated learning methods positively affects student learning outcomes in Islamic Education.